Antipersister strategies against stress induced bacterial persistence. (March 2022) - Kaushik, Vaishali; Sharma, Saroj; Tiwari, Monalisa; Tiwari, Vishvanath
Abstract: The increase in antibiotic non-responsive bacteria is the leading concern in current research oriented to eliminate pathogens. Nowadays, the excess use of antibiotics without specifically understanding the potentiality of killing pathogens and bacterial survival patterns has helped bacteria emerge indefatigably. Bacteria use various mechanisms such as resistance, persistence, and tolerance to ensure survival. Among these, persistence is a mechanism by which bacteria reside in their dormant state, bypassing the effects of treatments, making it crucial for bacterial survival. Persistent bacterial cells arise from the normal bacterial population as a slow-growing subset of bacteria with no metabolic flux. This behavior renders it to survive for a longer duration and at higher concentrations of antibiotics. They are one of the underlying causes of recurrence of bacterial infections. The present article explains the detailed molecular mechanisms and strategies of bacterial persistence, including the toxin-antitoxin modules, DNA damage, the formation of inactive ribosomal complexes, (p)ppGpp network, antibiotic-induced persistence, which are triggered by drug-induced stress. The article also comprehensively covers the epigenetic memory of persistence in bacteria, and anti-persistent therapeutics like antimicrobial molecules, synthetic peptides, acyldepsipeptide antibiotics, and endolysin therapy to reduce persister cell formation and control their frequency. These strategies could be utilized in combating the pathogenic bacteria undergoing persistence. Highlights: Persistent bacterial cells arise from the normal bacterial population as a slow-growing subset of bacteria that shows no metabolic flux. Molecular mechanisms of bacterial persistence includes toxin-antitoxin modules, DNA damage, inactive ribosomal complexes, (p)ppGpp network, antibiotic-induced persistence. Bacterial persistence has epigenetic memory. Anti-persistent therapeutics includes antimicrobial molecules, synthetic peptides, acyldepsipeptide antibiotic, endolysin therapy etc.